Nocturnal pulse rate and symptomatic response in patients with obstructive sleep apnoea treated with continuous positive airway pressure for one year - Pengo, Martino F.; Drakatos, Panagis; Kosky, Christopher; Williams, Adrian; Hart, Nicholas; Rossi, Gian Paolo; Steier, Joerg (Journal of Thoracic Disease, 2014)
Background: Obstructive sleep apnoea (OSA) is the most common form of sleep-disordered breathing and a known risk factor for cardiovascular disease. We hypothesised that in patients with OSA the characteristics of nocturnal pulse rate (PR) are associated with changes in blood pressure and daytime sleepiness, following commencement of continuous positive airway pressure (CPAP) therapy. Methods: Pulse oximetry data, demographics, daytime sleepiness and blood pressure were recorded at baseline and at one year follow up. Patients with OSA were grouped according to positive and negative changes in the PR (ΔPR) response during the first night of pulse oximetry before commencement of CPAP. Results: A total of 115 patients (58 with OSA and 57 matched subjects without OSA) were identified and included in the analysis. The scale of improvement in daytime sleepiness could be predicted by a negative or positive ΔPR, as recorded in the initial screening pulse oximetry [ΔESS –5.8 (5.1) vs. –0.8 (7.2) points, P